Reovirus-Induced Apoptosis Is Mediated by TRAIL - Clarke, Penny (American Society for Microbiology, 2000)
Members of the tumor necrosis factor (TNF) receptor superfamily and their activating ligands transmit apoptotic signals in a variety of systems. We now show that the binding of TNF-related, apoptosis-inducing ligand (TRAIL) to its cellular receptors DR5 (TRAILR2) and DR4 (TRAILR1) mediates reovirus-induced apoptosis. Anti-TRAIL antibody and soluble TRAIL receptors block reovirus-induced apoptosis by preventing TRAIL-receptor binding. In addition, reovirus induces both TRAIL release and an increase in the expression of DR5 and DR4 in infected cells. Reovirus-induced apoptosis is also blocked following inhibition of the death receptor-associated, apoptosis-inducing molecules FADD (for FAS-associated death domain) and caspase 8. We propose that reovirus infection promotes apoptosis via the expression of DR5 and the release of TRAIL from infected cells. Virus-induced regulation of the TRAIL apoptotic pathway defines a novel mechanism for virus-induced apoptosis.